2022
DOI: 10.3390/app12125874
|View full text |Cite
|
Sign up to set email alerts
|

Tea (Camellia sinensis): A Review of Nutritional Composition, Potential Applications, and Omics Research

Abstract: Tea (Camelliasinensis) is the world’s most widely consumed non-alcoholic beverage with essential economic and health benefits since it is an excellent source of polyphenols, catechins, amino acids, flavonoids, carotenoids, vitamins, and polysaccharides. The aim of this review is to summarize the main secondary metabolites in tea plants, and the content and distribution of these compounds in six different types of tea and different organs of tea plant were further investigated. The application of these secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 203 publications
0
13
0
Order By: Relevance
“…NFP Miang contains TP content of 100 mg GAE/g dw and TC content of 5 mg QE/g dw [14] , yet the results of this study indicated 1.5- and 2.5-times higher TP and TC contents, respectively. Green tea made from young tea leaves possessed TP ranging from 108.8 to 323.6 mg/g dw [13] , [38] , which was higher than that of oolong tea (103.5–297.3 mg/g dw), black tea (130.1–181.7 mg/g dw), and dark tea (78.2–162.9 mg/g dw) [13] . The main classes of flavonoids found in tea are flavanols and flavonols.…”
Section: Discussionmentioning
confidence: 88%
“…NFP Miang contains TP content of 100 mg GAE/g dw and TC content of 5 mg QE/g dw [14] , yet the results of this study indicated 1.5- and 2.5-times higher TP and TC contents, respectively. Green tea made from young tea leaves possessed TP ranging from 108.8 to 323.6 mg/g dw [13] , [38] , which was higher than that of oolong tea (103.5–297.3 mg/g dw), black tea (130.1–181.7 mg/g dw), and dark tea (78.2–162.9 mg/g dw) [13] . The main classes of flavonoids found in tea are flavanols and flavonols.…”
Section: Discussionmentioning
confidence: 88%
“…Tea leaves contain a large amount of flavonoids, which are the most important class of secondary metabolites in tea and one of the key factors determining its unique quality (Wang et al, 2022). Therefore, studying the key genes involved in flavonoid synthesis pathways can provide us with more insights into the formation of the unique qualities of tea.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most popular non-alcoholic beverages worldwide, tea contains a wide range of secondary metabolites beneficial to human health, such as polyphenols, alkaloids, and amino acids (Wang et al, 2022). With the unique qualities of tea plants ( Camellia sinensis ) attracting an increasing number of researchers to study various aspects of tea plants, such as secondary metabolites and phenotypic variations (Zhao et al, 2022; Wang et al, 2022; Liao et al, 2022), the omics dataset of Camellia sinensis has also become increasingly extensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids bind with intracellular proteins as well as soluble proteins present in the bacterial cell walls. Steroids are shown to form complexes with membrane lipids thus resulting in leakage [ 21 , 72 , 73 ]. These compounds present in In C. sinensis , may have contributed to the observed antibacterial effect.…”
Section: Discussionmentioning
confidence: 99%